Pesantren Agility in Community Economic Development - Fauroni, R Lukman; Quraisy, Mujahid (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2019)
Abstract This study aims to elaborate on the pesantren agility viewed from the aspects of sources and its implementation in the community economic development. The research uses the case study method. The research finds that pesantren agility is sourced from the traditional intellectual pesantren, the implemented integration of Islamic teaching and values in social-economic fields. Pesantren agility is the epicenter for the strength of socioeconomic functions, particularly the development of the community’s economy through the transformation and expansion of pesantren institutional services. The pesantren agility has been applied in community economic development according to the economic needs.AbstrakKajian ini bertujuan mengelaborasi agilitas pesantren dari aspek sumber dan implementasinya dalam pengembangan ekonomi komunitas. Metode penelitian menggunakan studi kasus. Ditemukan agilitas pesantren bersumber dari modal intelektual tradisi pesantren dan implementasi integrasi ajaran agama Islam dalam bidang sosial ekonomi. Agilitas pesantren merupakan episentrum bagi kekuatan fungsi sosial ekonomi khususnya dalam pengembangan ekonomi komunitas melalui transformasi perluasan fungsi kelembagaan pesantren. Agilitas pesantren diaplikasikan dalam pemberdayaan ekonomi komunitas sesuai kebutuhan dasar ekonominya.